Tracking and simulation of leader-follower formation control for two quadruped robots - Wong, Jun Heng (Nanyang Technological University, 2024)
This paper presents the performance comparison of the proportional-integral-derivative (PID) and sliding mode control (SMC) controllers and their control algorithms when it comes to leader-follower formation control of two quadruped (four-legged) robots. In the first stage of this project, literature review of papers related to leader-follower formation control of mobile robots were studied and analysed. The reasons behind the selection of PID and SMC will be discussed, along with the designs of the PID and SMC controllers. In the second stage of the project, the implementation and simulation of the PID and SMC controllers with regards to leader-follower formation control for two quadruped robots. Finally, the results and plots from the simulations will be gathered and studied for comparison. The objective of this paper is to test and compare the performance of each controller and their effectiveness in maintaining the desired formation between the leader and follower robots, while the leader robot is moving along the specified waypoints from start to end.